The possibility of palm oil mill effluent for biogas production - EDWI MAHAJOENO; BIBIANA WIDIYATI LAY; SURJONO HADI SUTJAHJO; SISWANTO SISWANTO (Society for Indonesian Biodiversity, 2008)
The world currently obtains its energy from the fossil fuels such as oil, natural gas and coal. However, the international crisis in the Middle East, rapid depletion of fossil fuel reserves as well as climate change have driven the world towards renewable energy sources which are abundant, untapped and environmentally friendly. Indonesia has abundant biomass resources generated from the agricultural industry particularly the large commodity, palm oil (Elaeis guiinensis Jacq.). The aims of the research were to (i) characterize palm oil mill effluent which will be used as source of biogas production, (ii) know the biotic and abiotic factors which effect POME substrate for biogas production by anaerobic digestion in bulk system. The results show that POME sludge generated from PT Pinago Utama mill is viscous, brown or grey and has an average total solid (TS) content of, 26.5-45.4, BOD is 23.5-29.3, COD is 49.0-63.6 and SS is 17.1-35.9 g/L, respectively. This substrate is a potential source of environmental pollutants. The biotic factors were kind and concentration of the inoculums, i.e. seed sludge of anaerobic lagoon II and 20% (w/v) respectively. Both physical and chemical factors such as pre-treated POME pH, pH neutralizer matter Ca (OH)2, temperature â‰¥40oC, agitation effect to increase biogas production, but in both coagulant concentration, FeCl2 were not.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: characteristic of POME, biogas production, biotic and abiotic factors, batch system, laboratory scale